👤

Efectuati :                    
a) 5 supra 6 + 7 supra 3 - 2ori 3supra4=
b)7supra10 - 2ori 2supra5 + 7supra4=
c)1ori 1supra6 - 5supra12 + 3 supra 8=
d) (- 13supra15) + 7supra6 + 1ori 4supra5=
e) 25supra12 + (-1ori 2supra9) - 7supra4=
f) (- 9supra8) - 1ori 2supra5 + 19supra10=




Răspuns :

[tex] \frac{5}{6} + \frac{7}{3} - 2* \frac{3}{4} = 5/6 + 7/3 - 6/4[/tex]  (Pe prima o amplifici cu 4 , pe a doua cu 8 iar pe a 3 cu 6 şi vine) 20/24 + 56/24 - 36/24 = [tex] \frac{20+56-36}{24} = \frac{76-36}{24} = \frac{40}{24} [/tex] (simplifici ambele cu 4 şi obţii) = [tex] \frac{10}{6} [/tex] ( mai simplifici cu 2) [tex] = \frac{5}{3} [/tex]